Revision of world Sphecomyia Latreille (Diptera, Syrphidae) - M. Moran, Kevin (Zookeys, 2019)
The 16 world species of Sphecomyia Latreille are revised, including seven previously undescribed species (S.cryptica Moran, sp. n., S.hoguei Moran, sp. n., S.interrupta Moran, sp. n., S.oraria Moran, sp. n., S.pseudosphecomima Moran, sp. n., S.sexfasciata Moran, sp. n., and S.weismani Moran, sp. n.). Descriptions, redescriptions, male genitalia photographs, distribution maps, and an illustrated key for all Sphecomyia are presented. DNA barcode data are provided for all 16 species with a cytochrome oxidase subunit I gene tree presented and discussed. Sphecomyiastat. rev. is redefined to represent the monophyletic lineage of species within subtribe Criorhinina possessing a bare, medial vitta extending ventrally from the oral margin in both sexes, a bare gena, a bare katepimeron, a scutellum with at least anterior margin densely pruinose, an anterior ventral half of vein C before crossvein h without setae, and a narrow intersection of vein R(1) with vein C. Three species groups of Sphecomyia are identified: the S.vittata group which possess pruinose scutellar vittae, the S.pattonii group which lack pruinose scutellar vittae, and S.metallica (Bigot), a hairy bee mimic with a completely pruinose scutum. Criorhinatsherepanovi Violovitsh is resurrected and transferred, along with Criorhinaaino Stackelberg, to the genus Sphecomyia: S.tsherepanovi (Violovitsh), comb. n. and S.aino (Stackelberg), comb. n.Criorhinametallica (Bigot) is designated as the senior synonym of C.lupina (Williston), not junior as improperly treated, and transferred to Sphecomyia: S.metallica (Bigot), comb. n. The species Sphecomyiafusca Weisman, S.nasica Osburn, and S.occidentalis Osburn are transferred to Criorhina Meigen: C.fusca (Weisman), comb. n., C.nasica (Osburn), comb. n., and C.occidentalis (Osburn), comb. n.